Dni wspomnienia zmarłych w tradycji wczesnochrześcijańskiej - Muc, Agnieszka (Śląskie Studia Historyczno-Teologiczne, 2010)
In the recently published Polish translation of De obitu Theodosii by St Ambrose of Milan, we find an inaccuracy concerning the days of commemoration of the dead. The Latin sentence: Et quia alii tertium diem et tricesimum, alii septimum et quadragesimum obseruare consuerunt informs us that some of the Christians observed the third and thirtieth day after death as the day of prayers for their departed while others observed the seventh and fortieth day. However, the Polish editors of the text suggest a different translation: the thirty-third and the forty- seventh day after death. This interpretation is correct from a grammatical point of view but it does not find any confirmation or support in other Christian literary sources. The Apostolic Constitutions – in its Greek, Coptic or Ethiopic version – recommend to Christians to celebrate the third, ninth and thirtieth (fortieth) day after death. The Egyptian monks and nuns from the St Shenoute of Atripe community observed the third, seventh and thirtieth day, as well as the anniversary in terms of prayers for the dead. The tradition of celebrating the third, seventh, ninth, thirtieth and fortieth day has its roots in pagan (mainly Greek-Roman) and Jewish culture and was easily adapted by the Christian Church, especially that some of these dates (third, seventh and thirtieth day) can relate to the text of the Bible. There were some differences between particular regions of the Christian world but it seems that neither of them observed the thirty-third or forty-seventh day as a commemoration of the dead.